Compatibility of Western and Islamic Models of Democracy A Comparative Analysis - Šrámek, Ondřej; Prorok, Vladimír, 1956-; Barša, Pavel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2009)
The thesis looks at compatibility of Islam and democracy in a new way. The main method is analysis of political ideologies. A number of models of democracy are identified in both the Western and Islamic context. These are then originally compared in a framework of classification by the source of political sovereignty and political action.
Vedoucí práce: Vladimír Prorok
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2010
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2010
Způsob přístupu: Internet
Keywords: politologie [obor disert. práce]; disertace; dissertations